The contribution in the training of professionals in Sociology: extension project in Lepanto-Puntarenas according to student experiences, 2020-2022 - García Chaves, Yamileth de los Ángeles (2023)
This article is derived from the project "Intersectional perspective of the coastal territory of Lepanto from community education, social participation and the strengthening of local capacities"; The main objective is to relate the experiences of the students linked to the project with the theoretical and methodological processes developed in the training process as professionals in Sociology. The methodology used was focused from the qualitative field with techniques such as interviews and discussion groups. The participants were six students who were linked to the project at the time of formulation and execution in the coastal-rural community of Lepanto in the period 2020-2022. The main results show the importance of the participation of students in these processes and the strengthening of social, disciplinary and university skills which are presented with the narrated experiences.